2011
DOI: 10.1264/jsme2.me10131
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dynamics of Anammox Bacteria in Estuarial Sediment of the Mai Po Nature Reserve Revealed by Analyzing the 16S rRNA and Hydrazine Oxidoreductase (hzo) Genes

Abstract: The community and population dynamics of anammox bacteria in summer (wet) and winter (dry) seasons in estuarial mudflat sediment of the Mai Po Nature Reserve were investigated by 16S rRNA and hydrazine oxidoreductase (hzo) genes. 16S rRNA phylogenetic diversity showed that sequences related to 'Kuenenia' anammox bacteria were presented in summer but not winter while 'Scalindua' anammox bacteria occurred in both seasons and could be divided into six different clusters. Compared to the 16S rRNA genes, the hzo ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 47 publications
6
52
2
3
Order By: Relevance
“…It is important to note, however, that fungal co-denitrification can also produce 14 N 15 N molecules similar to the anammox process. Since its first discovery in wastewater treatment systems, the anammox process has been reported as a major N2 source in various marine and fresh water and sediments (5,6,19,28,59,66,69,92,153). Anammox bacteria belong to several candidatus genera in the phylum Planctomycetes (113).…”
Section: Anaerobic Ammonium Oxidation (Anammox)mentioning
confidence: 99%
“…It is important to note, however, that fungal co-denitrification can also produce 14 N 15 N molecules similar to the anammox process. Since its first discovery in wastewater treatment systems, the anammox process has been reported as a major N2 source in various marine and fresh water and sediments (5,6,19,28,59,66,69,92,153). Anammox bacteria belong to several candidatus genera in the phylum Planctomycetes (113).…”
Section: Anaerobic Ammonium Oxidation (Anammox)mentioning
confidence: 99%
“…The hydrazine oxidoreductase genes (hzo gene) can be employed in phylogenetic diversity and functional analysis of anaerobic ammonium-oxidizing bacterium (anammox) in a community or an environment. The hzo genes are specific for the identification of anammox bacteria and can be used as a functional marker to give activity-based information regarding the anammox bacteria in a community [82]. Ozgun et al [83] identified and quantified anammox bacteria from waste water treatment plant by adopting a FISH-based approach with the PCR primers designed for the amplification of hzo specific genes.…”
Section: Techniques For Identifying Microorganisms Involved In the Anmentioning
confidence: 99%
“…Estes procariotos já têm sido detectados em sedimentos de manguezais e suas contribuições para a nitrificação nestes locais têm sido cada vez melhor compreendidas. Li et al (2011) compararam a presença de bactérias e arqueias oxidadoras de amônia em sedimentos de manguezal em diferentes profundidades, e sugerem que a abundancia de AOB é maior que AOA, especialmente na proximidade com plantas, o que pode indicar o papel mais importante da AOB sobre a nitrificação nestes locais. Os autores observaram ainda que existe uma forte correlação entre a abundancia do gene amoA e sua relação com a amônia, salinidade, pH dos sedimentos amostrados, indicando que arqueias amônio oxidantes seriam mais suscetíveis aos fatores ambientais.…”
Section: Nitrificaçãounclassified
“…Nos últimos anos, estudos com muitos locais marinhos anóxicos indicaram que o processo anammox é uma parte importante do ciclo do nitrogênio marinho 2005;KUYPERS et al, 2003;2005;RISGAARD-PETERSEN et al, 2004 (AMANNO et al, 2007;NAKAJIMA et al, 2008;ZHANG et al, 2007); o gênero 'Scalindua' geralmente é dominante em ecossistemas naturais, especialmente em ambientes marinhos WOEBKEN et al, 2008). Porém, o conhecimento sobre a estrutura da comunidade temporal de bactérias anammox em ecossistemas naturais ainda é limitado, especialmente em ecossistemas naturais com influências antropogênicas (LI et al, 2011).…”
Section: Hibridização Fluorescente In Situ (Fluorescence In Situ Hybrunclassified
See 1 more Smart Citation